Recent developments in optical fiber sensing using fiber bragg gratings - Kalli, Kyriacos; Webb, David J.; Jackson, David A. (My University, 1996)
We report on recent work on sensing using in-fiber Bragg gratings carried out in our laboratory. First, an alternative method of discriminating between temperature and strain effects using a conventionally written, in-fiber Bragg grating is presented. The technique uses wavelength information from the first and second diffraction orders of the grating element to determine the wavelength dependent strain and temperature coefficients, from which independent temperature and strain measurements can be made. Secondly, we describe an all-fiber, passive scheme for making extended range interferometric measurements based on the dual wavelength technique. A coherence turned interferometer network is illuminated with a single superfluorescent fiber source at 1.55 mm and the two wavelengths are synthesized at the output by means of chirped fiber Bragg gratings.
Keywords: Bragg gratings; Diffraction gratings; Fiber optics; Fluorescence